Evaluation of HPV type‐replacement in unvaccinated and vaccinated adolescent females—Post‐hoc analysis of a community‐randomized clinical trial (II). Issue 12 (12th February 2018) - Gray, Penelope; Palmroth, Johanna; Luostarinen, Tapio; Apter, Dan; Dubin, Gary; Garnett, Geoff; Eriksson, Tiina; Natunen, Kari; Merikukka, Marko; Pimenoff, Ville; Söderlund‐Strand, Anna; Vänskä, Simopekka; et al.
Abstract : Efficacy of human papillomavirus (HPV) vaccines promises to control HPV infections. However, HPV vaccination programs may lay bare an ecological niche for non‐vaccine HPV types. We evaluated type‐replacement by HPV type and vaccination strategy in a community‐randomized trial executed in HPV vaccination naïve population. Thirty‐three communities were randomized to gender‐neutral vaccination with AS04‐adjuvanted HPV16/18 vaccine (Arm A), HPV vaccination of girls and hepatitis B‐virus (HBV) vaccination of boys (Arm B) and gender‐neutral HBV vaccination (Arm C). Resident 1992‐95 born boys (40, 852) and girls (39, 420) were invited. 11, 662 boys and 20, 513 girls were vaccinated with 20–30% and 45–48% coverage, respectively. HPV typing of 11, 396 cervicovaginal samples was performed by high throughput PCR. Prevalence ratios (PR) between arms and ranked order of HPV types and odds ratio (OR) for having multiple HPV types in HPV16 or 18/45 positive individuals were calculated. The ranked order of HPV types did not significantly differ between arms or birth cohorts. For the non‐HPV vaccinated 1992–1993 birth cohorts increased PR, between the gender‐neutral intervention versus control arms for HPV39 (PRA 1.84, 95% CI 1.12–3.02) and HPV51 (PRA 1.56, 95% CI 1.11–2.19) were observed. In the gender‐neutral arm, increased clustering between HPV39 and the vaccine‐covered HPV types 16 or 18/45 (ORA16 = 5.1, ORA18/45 = 11.4) was observed in the non‐HPV vaccinated 1994–1995 birth cohorts. Comparable clustering was seen between HPV51 and HPV16 or HPV18/45 (ORB16 = 4.7, ORB18/45 = 4.3), in the girls‐only arm. In conclusion, definitively consistent postvaccination patterns of HPV type‐replacement were not observed. Future occurrence of HPV39 and HPV51 warrant investigation. Abstract : What's new? Vaccination against high‐risk human papilloma virus (HPV) strains is efficacious, but possible resurgence of non‐targeted viral strains is a concern. The authors performed a community‐randomized study with 20–50% vaccination coverage in 1992–95 birth cohorts of 80, 000 adolescents. They compared gender‐neutral or girls‐only HPV16/18 vaccination or hepatitis B‐virus vaccination in 11 communities, and a consistent pattern of HPV type‐replacement was not found. However, occurrence of HPV39 and HPV51 types warrants further observation in the future.